The Essence of a Teacher: Analyzing the Concept of "Muallim" in the Quran - Sumarno Sumarno; Alan Lutfi Gesang Saputra; Akhlis Mu’ammar Rifqi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
The history of humanity's quest for knowledge has given rise to unique and intriguing perspectives in the Western world, particularly concerning the debate between empiricism and rationalism. However, in contemporary discourse, the assertion "Experience is the Best Teacher" is being contested, notably by John C. Maxwell, who argues that experience alone is insufficient as a teacher unless it is evaluated. This article compares Western views with the Islamic perspective, asserting that the Quran is the highest source of knowledge. The primary focus is on the concept of "muallim" or teacher in the Quran, highlighting that Allah imparts all knowledge through the Prophet and other messengers. This research employs library research methods to establish theoretical and conceptual foundations. Findings reveal that a true muallim is a devout person who adheres to Allah, continuously teaches and learns from the scripture. In conclusion, the Quranic teacher plays a more profound role as a source of knowledge and spiritual guidance. The article proposes guidelines for modern muallims, including a belief in Allah as the source of knowledge, emulating the Prophet, avoiding harmful activities, and embracing beneficial teachings. Thus, understanding the concept of "muallim" in the Quran can serve as a basis for developing effective and meaningful teaching methods in contemporary contexts.